Lack of TXNIP protects β-cells against glucotoxicity. (19th September 2008) - Shalev, Anath
Abstract : Glucotoxicity plays a major role in pancreatic β-cell apoptosis and diabetes progression, but the factors involved have remained largely unknown. Our recent studies have identified TXNIP (thioredoxin-interacting protein) as a novel pro-apoptotic β-cell factor that is induced by glucose, suggesting that TXNIP may play a role in β-cell glucotoxicity. Incubation of INS-1 β-cells and isolated primary mouse and human islets at high glucose levels led to a significant increase in TXNIP as well as in apoptosis. Very similar results were obtained in vivo in islets of diabetic mice. To determine whether TXNIP plays a causative role in glucotoxic β-cell death, we used TXNIP-deficient islets of HcB-19 mice harbouring a natural nonsense mutation in the TXNIP gene. We incubated islets of HcB-19 and C3H control mice at low and high glucose levels and assessed them for TXNIP expression and apoptosis. Interestingly, whereas in C3H islets, high glucose levels led again to significant elevation of TXNIP and apoptosis levels as measured by TUNEL (terminal deoxynucleotidyl transferase-mediated dUTP nick-end labelling) and cleaved caspase 3, no increase in apoptosis was observed in TXNIP-deficient HcB-19 islets, indicating that TXNIP is required for β-cell death caused by glucotoxicity. Thus inhibition of TXNIP protects against glucotoxic β-cell apoptosis and therefore may represent a novel therapeutic approach to halt diabetes progression.